Zona de Remanso: exercícios de permanência - Normando, Filipe Acácio (2017)
The urgency of this research is based on an artistic investigation about the action of staying in the city of Fortaleza. In the context of the extreme social inequality and the numerous slaughterings that took place between the years 2015 and 2016, during the period of the research, I develop permanence exercises on the coast of the city, more specifically the retaining walls built between the sea and the city. In developing these exercises, whose reflections are also present in this text, I concentrate on conjugating the verb / procedure of permanence. It is not an out of body exercise. In treating permanence as a gesture of resistance in space, which does not settle, I perceive the delicate balance between going and staying.